2006
DOI: 10.4067/s0718-19572006000200007
|View full text |Cite
|
Sign up to set email alerts
|

Variación temporal en la dieta del congrio colorado, Genypterus chilensis (Guichenot, 1881) frente al litoral de Talcahuano, Chile (36º32’S - 36º45’S)

Abstract: Variación temporal en la dieta del congrio colorado, Genypterus chilensis (Guichenot, 1881) frente al litoral de Talcahuano, Chile (36º32'S-36º45'S) Temporal variation in the diet of the red ling, Genypterus chilensis (Guichenot, 1881) in the coast off Talcahuano, Chile (36º32'S-36º45'S

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 5 publications
1
11
0
2
Order By: Relevance
“…The results obtained from 621 average masses per season for an estimation of between 11 to 48 females, confirm that G. chilensis is a partial spawner, as Chong et al (2006) had indicated, and like G. blacodes and Gadus morhua (Paredes & Bravo, 2005;FAO, 2008). In captivity, it is important to identify and separate each female to have a specific knowledge of the volume of the mass and the number of eggs, in order to comfirm the release of more than two masses per day and the average of 13 to 56 masses/female/season.…”
supporting
confidence: 68%
See 2 more Smart Citations
“…The results obtained from 621 average masses per season for an estimation of between 11 to 48 females, confirm that G. chilensis is a partial spawner, as Chong et al (2006) had indicated, and like G. blacodes and Gadus morhua (Paredes & Bravo, 2005;FAO, 2008). In captivity, it is important to identify and separate each female to have a specific knowledge of the volume of the mass and the number of eggs, in order to comfirm the release of more than two masses per day and the average of 13 to 56 masses/female/season.…”
supporting
confidence: 68%
“…Its geographical distribution extends from Paita in Peru to Cape Horn in southern Chile (Kong et al, 1988). It mainly inhabits in coastal bodies of water at depths that generally range between 20 to 150 m; it is a benthic species of the continental shelf usually found on rocky substrates, feeding on fish, crustaceans, and mollusks (Chong et al, 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Small groups of fishers harvest congrio close to home but outside of any management areas (usually half a km from the coast or beyond). Congrio colorado live from the continental shelf up to 400 m depths; they consume mainly crustaceans as well as fish and mollusks (Chong et al 2006). The congrio colorado harvest peaks from October to February although the fish is harvested year-round.…”
Section: Figmentioning
confidence: 99%
“…Los estudios de alimentación en esta especie y otras del mismo género, revelan una dieta carnívora eurifágica de variada composición específica, con un gran número de ítems presa con claras preferencias alimenticias por organismos pelágicos tales como crustáceos de pequeño tamaño, como langostino colorado (Pleuroncodes monodon), mysidáceos y eufáusidos; entre los peces destacan la presencia de Normanichthys crockeri, Clupea (Strangomera) bentincki, Engraulis ringens, y en menor proporción calamares (Loligo gahi) (Chong et al, 2006). Los reproductores silvestres en cautiverio se alimentan con trozos de peces grasos (Trachurus murphy, Scomber japonicus peruanus, Clupea (S.) bentincki o jibias Dosidiscus gigas) (Vega et al, 2012).…”
Section: Introductionunclassified